Temporal changes in neutropenic blood culture isolates and disease associations: a single centre series of 1139 episodes. Issue 8 (August 2017) - Lucas, Nathanael; Humble, Michael; Sim, Dalice; Balm, Michelle; Carter, John; Weinkove, Robert
Abstract: Neutropenic infections are life‐threatening and require empiric antibiotic treatment. We examined 1139 blood culture isolates from our institution over a 36‐year period from neutropenic patients to examine temporal trends and disease associations. Positive associations were found between viridans streptococci and acute myeloid leukaemia, coagulase negative staphylococci and acute lymphoblastic leukaemia and Pseudomonas aeruginosa and indolent B‐cell malignancies.